The Idea of Universal History in Greece : From Herodotus to the Age of Augustus - Alonso-Núnez, J.M. (Brill Book Archive Part 1, ISBN: 9789004472495., 2002)
This is an expanded version of a lecture given in the Departments of History and Classics at Harvard in 1998. Starting from a methodological point of view, this book show the evolution of the idea of world history through the works of Herodotus, Thucydides, Xenophon, Ctesias, Ephorus, Polybius and others up to the historians of the Augustan epoch.